2022
DOI: 10.1590/1806-9282.20220295
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune-inflammation index as a novel predictor of atrial fibrillation after off-pump coronary artery bypass grafting

Abstract: OBJECTIVE: This study aims to examine the predictive role of systemic immune-inflammation index on postoperative new-onset atrial fibrillation in patients undergoing off-pump coronary artery bypass grafting. METHODS: A total of 722 patients undergoing elective off-pump coronary artery bypass grafting between January 2017 and September 2021 were included in this study and divided into two groups as the atrial fibrillation group (n=172) and the non-atrial fibrillation group (n=550). Both groups were compared in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Two recent studies [16,17] have, indeed, demonstrated significant associations between RWD, the sensitive marker of increased red cells turnover [18,19], and AF in general populations. In addition, Topal and coworkers [20] have recently proved that the median values of white blood cell, platelet, neutrophil, neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, resulted significantly greater in cases with AF and undergoing off-pump coronary artery bypass grafting than in those in the non-AF group. Likewise, Sayin and coworkers [21] have also documented that PLT counts accompanied by the evaluation of other immune-inflammatory indexes can predict new onset AF in cases affected by acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 97%
“…Two recent studies [16,17] have, indeed, demonstrated significant associations between RWD, the sensitive marker of increased red cells turnover [18,19], and AF in general populations. In addition, Topal and coworkers [20] have recently proved that the median values of white blood cell, platelet, neutrophil, neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, resulted significantly greater in cases with AF and undergoing off-pump coronary artery bypass grafting than in those in the non-AF group. Likewise, Sayin and coworkers [21] have also documented that PLT counts accompanied by the evaluation of other immune-inflammatory indexes can predict new onset AF in cases affected by acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 97%
“…Open heart surgery and CECC, however, contribute to evocating local and systemic inflammation. Systemic inflammation can cause diminished visceral blood flow resulting in mucosal ischemia, edema, and impaired mucosal transport [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Concerning local inflammation, research performed over the past 5 years evidence that atrial cardiomyocytes have diverse inflammatory signaling pathways that are demonstrated to be activated in both animal models and AF patients [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic inflammation can cause diminished visceral blood flow resulting in mucosal ischemia, edema, and impaired mucosal transport [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Concerning local inflammation, research performed over the past 5 years evidence that atrial cardiomyocytes have diverse inflammatory signaling pathways that are demonstrated to be activated in both animal models and AF patients [ 12 , 13 , 14 , 15 , 16 , 17 ]. Such growing evidence on the crucial role of inflammation in POAF has also led to investigations on hematological indices as potential prognostic and predictive biomarkers for POAF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations